2012
DOI: 10.5114/pdia.2012.31493
|View full text |Cite
|
Sign up to set email alerts
|

The role of extracellular matrix metalloproteinases and their inhibitors in allergic diseases

Abstract: A b s t r a c tDuring the migration to the site of inflammation, allergic inflammatory cells must overcome several structures that constitute an impregnable barrier under normal conditions. One such structure is the extracellular matrix responsible for closely filling the intercellular space of tissues. The loosening of this tight structure by the activity of specific tissue enzymes, i.e. extracellular matrix metalloproteinases (MMPs), enables the influx of effector cells to the site of inflammation, thus faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The activation of TGF-β is mediated by thrombospondin, plasmin, integrins and THY-1 (CD90), as well as matrix metalloprotease 9. Not only is TGF-β believed to initiate the production of extracellular matrix components (including collagen, fibronectin and proteoglycans) but also it inhibits their degradation due to interactions with matrix metalloproteinases and stimulation of synthesis of their inhibitors [ 12 , 16 , 17 ]. It has been shown that TGF-β increases fibroblast susceptibility for apoptosis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The activation of TGF-β is mediated by thrombospondin, plasmin, integrins and THY-1 (CD90), as well as matrix metalloprotease 9. Not only is TGF-β believed to initiate the production of extracellular matrix components (including collagen, fibronectin and proteoglycans) but also it inhibits their degradation due to interactions with matrix metalloproteinases and stimulation of synthesis of their inhibitors [ 12 , 16 , 17 ]. It has been shown that TGF-β increases fibroblast susceptibility for apoptosis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Korostoff et al [8] demonstrated an expression of latent forms of MMP-2 and MMP-9 in gingival biopsies taken from healthy individuals and patients with periodontitis. In turn, the active form of MMP-2 was present only in material collected from patients with periodontitis [9].…”
Section: Mediators Of Inflammation In Periodontal Diseasesmentioning
confidence: 99%
“…Numerous MMPs, including MMP-2, participate in many physiologic processes, such as embryogenesis, angiogenesis, connective tissue regeneration. Metalloproteinases activity increases in many pathologic conditions, such as malignancies, autoimmune diseases, cardiovascular diseases, inflammatory diseases, skin diseases (dermatitis herpetiformis, pemphigus vulgaris, bullous pemphigoid, atopic dermatitis) and allergic diseases (bronchial asthma, urticaria, allergic rhinitis) [ 5 , 14 ].…”
Section: Introductionmentioning
confidence: 99%